Evaluation of macula, optic nerve and choroid in children with joint hypermobility (Annals of Medical Research, 2021)
Aim: To evaluate the macula, optic nerve and choroid layer by using Spectral Domain (SD)-OCT in children with joint hypermobility (JH)Material and Methods: In this cross-sectional case control study, 25 eyes of 25 children with JH diagnosed by rheumatological examination and 37 eyes of 37 healthy children were evaluated. Images were taken with SD -OCT. Two groups were compared in terms of mean central macular thickness, macular volume, ganglion cell complex (GCC) thickness, retina nerve fiber layer (RNFL) thickness and choroidal thickness (CT). CT was measured at the fovea; other CT measurements were taken 1,000 µm away from the fovea at the nasal and temporal regions and 1000 µm away from the optic disc at the nasal and temporal regions.Results: Mean subfoveal CT was 293.85±40.74 µm in JH group and 301.66±49.47 µm in the control group (p=0.548). There was no significant difference regarding to the mean macular and peripapillary CT values of all regions (P >0 .05 for all points). Moreover, the mean thicknesses of the RNFL, macula, and GCC did not differ between the two groups.Conclusion: This study showed that CT of children with JH is similar to those of healthy controls. In addition, there was no difference in macular thickness, RNFL and GCC between the two groups. These findings suggest that posterior segment structures are not affected in individuals with JH. Keywords: Joint hypermobility; choroid; macula; optic nerve.
Keywords: Joint hypermobility; choroid; macula; optic nerve.